THE RELATIONSHIP BETWEEN THERAPEUTIC COMMUNICATION AND THE ROLE OF NURSE EDUCATORS WITH THE LEVEL OF PATIENT SATISFACTION IN THE INPATIENT WARD - Utami, Langgeng; Romiko; Sri Yulia (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
The inconsistency of the implementation of therapeutic communication and patient education by nurses at the Palembang Harbor Hospital is evident from patient complaints regarding unclear explanations of procedures, incomplete information, and nurse responses that are considered less empathetic, so that these conditions are suspected to affect the level of patient satisfaction and need further research to determine the extent to which therapeutic communication and education provided by nurses are related to patient satisfaction in the inpatient ward. The purpose of this study was to determine the relationship between therapeutic communication and the role of nurse educators with the level of patient satisfaction in the inpatient ward of the Palembang Harbor Hospital. This study used a cross-sectional approach. The sample of this study was 30 patients treated in the inpatient ward using an accidental sampling technique. Data collection used a questionnaire on therapeutic communication, the role of nurse educators and patient satisfaction. The results showed that therapeutic communication and the role of nurse educators were significantly related to patient satisfaction, indicated by a p value = 0.003 in therapeutic communication and p = 0.001 in the role of educators, with the majority of patients (76.7%) reporting high satisfaction so that the quality of communication and nurse education were the main factors determining patient satisfaction. It can be concluded that there is a significant relationship between therapeutic communication and the level of patient satisfaction and there is a significant relationship between the role of nurse educators and the level of patient satisfaction